Seismic Loss Estimation in Pre-1970 Residential RC Buildings: The Role of Infills and Services in Low–Mid-Rise Case Studies - Del Gaudio, Carlo; De Risi, Maria Teresa; Scala, Santa Anna; Verderame, Gerardo Mario (Frontiers in Built Environment, 2020)
The lesson-learned after the recent earthquakes highlighted the key role played by infills and services in damage and losses estimation of Reinforced Concrete (RC) buildings. Thus, their influence in seismic performance and loss estimation of selected case-study RC buildings is herein thoroughly analyzed. The selection of the case studies aims to be representative of Italian existing buildings built before 1970, considering a different number of stories and design typologies. The seismic response of the case-study buildings is numerically analyzed by means of nonlinear static pushover (PO), considering a lumped plasticity approach with a quadri-linear flexural response for beam/column elements (properly calibrated for RC elements reinforced with plain bars), and a tri-linear compressive-only axial response with diagonal concentric struts for infill panels (empirically derived from experimental data on hollow clay masonry wall). The economic loss estimation is carried out via a component-based methodology relying on the main repairing activities and resultant costs required for the refurbishment of infills and services for different damage levels. Accordingly, damage analysis is herein performed, given the intensity measure, from the comparison between Interstorey drift demand from PO analysis and drift-based fragility functions specific for masonry infills. Loss curves, relating the total building repair cost to peak ground acceleration (PGA), are presented and compared among the analyzed case-study buildings to show their trends and quantify the incidence of infills and services with respect to the reconstruction cost. The comparison of these outcomes with those recently found in the literature emphasizes the robustness of the considered approach and the reliability of the hypotheses about damage and loss assessment.